2019
DOI: 10.1088/1742-6596/1375/1/012056
|View full text |Cite
|
Sign up to set email alerts
|

Business architecture planning with TOGAF framework

Abstract: Enterprise TOGAF architecture development methodology. TOGAF is a detailed method in its stages to build a new business process architecture and information system. The results in welcoming the era of industrial revolution, education in Indonesia especially higher education, one of which is obtained at STIKES strives to follow the development of information technology. One of the existing STIKES in East Java is a college that has a vision and mission according to the development of information technology. but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…It consists of a framework called the Architecture Development Method (ADM). It is a large part of TOGAF that indicates how an enterprise architecture can meet specific business needs [30]. TOGAF is an enterprise architecture framework that has the objective of designing, planning and organizing the infrastructure of the IT system [31].…”
Section: State Of the Art On Enterprise Architecture Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…It consists of a framework called the Architecture Development Method (ADM). It is a large part of TOGAF that indicates how an enterprise architecture can meet specific business needs [30]. TOGAF is an enterprise architecture framework that has the objective of designing, planning and organizing the infrastructure of the IT system [31].…”
Section: State Of the Art On Enterprise Architecture Frameworkmentioning
confidence: 99%
“…TOGAF is an enterprise architecture framework that has the objective of designing, planning and organizing the infrastructure of the IT system [31]. (Sofyana, L., and al., 2019) generated enterprise architecture planning in a college that has a vision and mission considering the development of IT technologies with TOGAF [30]. The latter showed that the approach led to an effective outcome.…”
Section: State Of the Art On Enterprise Architecture Frameworkmentioning
confidence: 99%
“…System Enterprise architecture is a single entity that deals with the principles, methods and a model that is used as the design, and realization of an organizational structure, business processes, information systems, and infrastructure of an organization. The enterprise architecture framework is known as a thinking framework, the use of a thinking framework is better judged to accelerate and simplify architectural development, ensure complete coverage of design solutions and ensure selected architecture that enables future development in response to business needs [12]. Enterprise Architecture is a representation of the structure and behavior of a company's business processes.…”
Section: Enterprise Architecturementioning
confidence: 99%
“…The history of the development of the TOGAF began before 1990 which was made by the United States Department of Defense which refers to TAFIM (Technical Architecture Framework for Information Management). In 1990, the TOGAF was taken by the Open Group and in 1995 specifications about the TOGAF were first introduced in general [17].…”
Section: The Open Group Architecture Frameworkmentioning
confidence: 99%